Gambaran Indeks Massa Tubuh (IMT) pada Mahasiswa - Andry Pratama; Zulfahmidah Zulfahmidah (Indonesian Journal of Health, 2021)
Body Mass Index (BMI) is a simple tool or way to monitor the nutritional status of adults, especially those related to underweight and overweight. Body Mass Index is defined as a person's body weight in kilograms divided by his height in meters (kg / m2). The objective of the research is to determine the description of the Body Mass Index (BMI) in students based on physical activity, duration of daily exercise, frequency of exercise each week. This research is a quantitative study with a cross sectional approach. Data collection was carried out through questionnaires. The research sample was the sample with the overall BMI and control was the ideal BMI sample. The sample obtained was 77 samples of students of the Faculty of Medicine, University of Muslim Indonesia. The results showed that there were 10 respondents with an under nutrition BMI (13.0%), 50 respondents (64.9%) with ideal BMI, 11 respondents (14.3%) with overnutrition BMI. respondents with BMI of obesity / fat were 6 people (7.8%). The lowest level of activity in the heavy activity category was 7 respondents and the highest was in the light activity category with 58 respondents. The lowest level of exercise duration is in the category> 30 minutes as many as 27 respondents and the highest level of exercise duration is in the <30 minutes category, which is 58 respondents. The lowest level of exercise frequency is in the category> 5 times as many as 5 respondents and the highest level of exercise frequency is in the 1-2 times category, namely as many as 61 respondents. Conclusion: Physical activity, exercise duration and a good frequency of exercise can provide an ideal Body Mass Index.